Integrated Zakat Governance Model in Malaysia: Lessons for Zakat Management Reform in Indonesia Based on Efficiency Analysis and Mixed-Methods - Agus Taruno; Muhammad Said; Rizqon Halal Syah Aji; Rini Rini (Universitas Pendidikan Ganesha, 2025)
This study aims to identify best practices of Malaysian integrated zakat governance that can be transferred to Indonesian zakat management reform. This study compares zakat governance in Malaysia and Indonesia using a mixed-methods sequential explanatory design that combines quantitative DEA analysis and NVivo qualitative analysis. The results show that Malaysia achieves 3.2 times higher efficiency through an integrated institutional structure, strong fiscal incentives (including direct tax deductions), and a mature digital infrastructure. The collection of zakat per muzaki in Malaysia reached Rp 9.2 million, compared to Indonesia at Rp 226 thousand, indicating a substantial difference in individual-level contribution. The research develops an Integrated Zakat Governance Model (MTKZ) for Indonesian reform, featuring a federal-coordinated architecture, fiscal reform, integrated digital platforms, and professionalization of human resources. The findings challenge the assumption that zakat management effectiveness depends solely on demographic and religious factors, demonstrating that institutional governance architecture is a critical determinant.